(untitled) (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2025)
This study explains the price interactions in the housing market using a spatial framework. Introduced spatial model connects the average Euclidean distance between social and luxury houses to house pricing. When a cheaper alternative exists, even if it’s not perfect, there will be pressure on the prices of expensive goods or services. In addition to this, the cost, and hence the price of houses, depends on the price of lots. Lots closer to highly priced house clusters tend to be more expensive. Concerning social justice, the social planner aims to produce as many social houses as possible. Also, in line with macroeconomic stability aim, government tries to keep the house price index low. These goals, however, presents a dual optimization problem. The planner must allocate the social houses far away from luxury houses to maximize their number. On the other hand, in order to keep the housing price index low, social houses must be built near to luxury houses in order to create a serious price pressure. The model introduced in this paper provides a method for balancing social fairness with economic viability. Introducing models with dynamic factors such as population growth and migration could be considered for further research. Also, testing the models in different urban areas could be a good option. By connecting spatial planning with economic and social goals, this study adds an analytical aspect to sustainable urban design and fair housing policy.